2020
DOI: 10.1088/0256-307x/37/1/016102
|View full text |Cite
|
Sign up to set email alerts
|

The Unexpected Stability of Hydrazine Molecules in Hydrous Environment under Pressure*

Abstract: The incomplete decomposition product of metastable hydrazine (N2H4) instead of the energetically favorable ammonia (NH3) upon decompression is one drawback in applications of energetic material oligomeric hydronitrogens. We explore the stability of hydrazine molecules in hydrazine hydrate (N2H4·H2O) under pressure in diamond anvil cells (DACs) combined with in situ Raman spectroscopy and synchrotron x-ray diffraction (XRD) measurements. The results show that one NH2 branch forms NH3 group by hydrogen bonds bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In the first compression run, the liquid hydrazine hydrate sample was compressed to the ultimate pressure of 16.6 GPa, which showed consistent behaviors with previous research results. 10 The in situ Raman spectra of hydrazine hydrate at evolutionary pressures are collected in Figure 1. After loading, the sample was in the liquid state with broad intramolecular bands of N 2 H 4 and H 2 O molecules up to 3.5 GPa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first compression run, the liquid hydrazine hydrate sample was compressed to the ultimate pressure of 16.6 GPa, which showed consistent behaviors with previous research results. 10 The in situ Raman spectra of hydrazine hydrate at evolutionary pressures are collected in Figure 1. After loading, the sample was in the liquid state with broad intramolecular bands of N 2 H 4 and H 2 O molecules up to 3.5 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Raman spectroscopy measurement revealed that the diverse hydrogen-bond networks played a vital role in structural stability and further isostructural phase transition. In hydrazine monohydrate, the sample also formed a pure component complex at high pressures, 10 and interaction of hydrazine and water molecules was continuously reinforced by the hydrogen bonds under compression up to 36 GPa. However, upon unloading to about 2.3 GPa, pure hydrazine had extracted from the complex solid, evidenced by the appearance of several characteristic stretching peaks, indicating a drastic change in the stoichiometric proportion of the sample with the abrupt breakup of H-bonds between heterogeneous molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high pressure thus offers exciting opportunities for discovering new materials that do not exist under ambient conditions. [34][35][36][37][38][39][40] Highpressure does not necessitate the destruction of the MF 6 octahedron in MF 3 systems. In practice, the pressure-induced structural evolution is only the cooperative tilting of the MF 6 octahedra, [41][42][43] which can be summarized as follows: (i) an elongation of the MF 6 octahedra along the c axis leads to a small octahedral strain, (ii) the MF 6 octahedral strain disappears, and (iii) MF 6 octahedral elongation occurs along the a axis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the high-pressure technology is a powerful tool for tuning the bandgaps of materials, investigating the structures of 2D materials such as the superconductive MoS 2 , MoSe 2 and ReSe 2 . [11,12] In a previous work, a hexagonal type to an NaCl-type phase transition at around 29 GPa in the bulk sample has been demonstrated, but the pressure dependence of few-layered GaSe has not been reported yet. More-over, many problems arising from its special oxidation mechanism in ambient atmosphere limit their applications.…”
mentioning
confidence: 99%